COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE BEFORE AND DURING THE COVID-19 PANDEMIC - Ulfah Rahmawati; Kholilah Kholilah (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2023)
This study aims to determine the financial performance before and during the Covid-19 pandemic in Indonesia. This study used a comparative quantitative method with Kruskal Wallis test to compare the financial performance of 312 companies on the Indonesian stock exchange. The results of this study show differences in liquidity, solvency, profitability, and financial activities of companies before and during the Covid-19 pandemic. This difference is due to the conservative nature of the company to expand its business and allocate investments in instruments or sectors that do not have high risks. This condition causes many companies to make efficiencies by breaking off employment relations or reducing employee salaries, which impacts people's purchasing power. The decline in people's purchasing power and mobility restrictions decreased the company's income. This study could not find the difference between the liquidity ratio and the current and quick ratio. This result allows the use of other liquidity measurements such as the cash turnover ratio because it shows the relative value between the value of net sales to net working capital.